Awakening, Efficacy, and Action: A Qualitative Inquiry of a Social Justice-Infused, Science Education Program. - Kozan, Saliha; Blustein, David L.; Barnett, Michael; Wong, Catherine; Connors‐Kellgren, Alice; Haley, James; Patchen, Amie; Olle, Chad; Diemer, Matthew A.; Floyd, Ava; Tan, R. P. Benjamin; Wan, Deborah (Analyses of Social Issues & Public Policy, 2017)
This article describes an innovative application of a social justice-infused pedagogy to an out-of-school program for urban high school students. Using an interdisciplinary framework, the program featured a coherent synthesis of science, technology, engineering, and math (STEM) education, highlighting environmental and food justice perspectives; social justice education; and career and college planning. We used qualitative content analysis to analyze two separate interviews with six female and three male students of color ranging in age from 15 to 18 with an average age of 16.1 ( SD=1.26) across an approximately 10-month time span. Utilizing a model of critical consciousness development as our organizing framework, we explored the students' understanding of environmental and food justice issues. Participants indicated that they were actively engaged in learning about food and environmental justice, exploring STEM careers, and investigating the various ways that social justice is manifested in their lives. Implications for social justice and STEM education interventions as well as broader public policies are discussed.